Assessing the implications of local governance on street trading: a case of Cape Town's inner city - Mwasinga, Ben (School of Architecture, Planning and Geomatics, 2014)
The significance of the informal economy in developing countries has long been established however, this is not reflected in the governance of informal economic activities in these states. Although restricted the informal economy contributes significantly to the Gross Domestic Product of developing countries and to the reduction of unemployment. In South Africa the abolishment of apartheid led to the rapid urbanisation of major cities and with it an increase in street trade which is recognised under the Business Act No. 76 of 1991. However, many authors have argued that street trade is still restricted in urban centres and remains marginalised due to the restrictive governance approaches adopted by local authorities. Hence the purpose of this study is to assess the implications of Cape Town's local governance approach for street traders in the inner city. Using a qualitative research method, the case study, this study explores the lived experiences of traders in the inner city and their relationship with the local authority . The study used interviews, primary document reviews and direct observations as the research techniques to gather information and explore the implications of the governance approach adopted by the local authority on trader's livelihoods and working experiences. The local authority was found to pursue urban planning initiatives, such as the redevelopment of Cape Town Station, in order to attract investment and formal businesses at the expense of street traders. It was found that the local authority's governance approach to street trading serves to marginalise traders and does not include them in urban planning and development. Furthermore the study established a lack of inclusive planning in the formulation of policy and implementation of strategies that impact on trader's livelihoods.